Synthesis, characterization and study of mercury(II) complexes with phosphine and heterocyclic thiones - Ahmed S. M. Al-Janabi (Tikrit Journal of Pure Science, 2023)
Many new mixed ligand complexes of mercury(II) have been synthesized with LH = 4,5-(diphenyl)-1,2,4-triazole-3-thione (diptSH) and tertiary phosphines as co-ligands. The compounds have been characterized by elemental analyses, IR, UV–Vis, molar conductivity, and NMR spectroscopy. In the binuclear complexes (2-5), both Hg atoms have tetrahedral geometry, the Hg atom bonded to three halide ions and one thione ligand (LH) through the sulfur atom. The complex (6) show that thiolate ligand(diptS-) is coordinated as monodentate through the sulfur atom. The dppm behave as bidentate bridging ligand to bonded two Hg(II) ions in the complex (7), Whereas in the complexes (7-10), the thionlate ligand bonded as a monodentate fashion via the sulfur atom, while the diphosphines ligands coordinated as bidentate chelating ligands, and the geometry around the Hg center ion is tetrahedral. And in the complexes (11 and 12), the phosphine bonded as monodentate ligand, and the thionlate bonded via the sulfur atom as monodentate to give tetrahedral complexes